Realization of red plasmon shifts by the selective etching of Ag nanorods. Issue 45 (2nd November 2020) - Zhu, Xingzhong; Xu, Juan; Yun, Qinru; Wang, Changshun; Ruan, Qifeng; Kan, Caixia
Abstract : The red plasmon shifts is realized through selective deposition of Au atoms and etching of Ag atoms on the Ag nanorods. Abstract : The preparation of small-sized nanostructures with the plasmon wavelength beyond ∼1000 nm is strongly needed. Herein we report on the deposition and galvanic replacement process on Au nanobipyramid-embedded Ag nanorods with the assistance of the added Au precursor to form Ag nanobones, leading to the resultant red plasmon shifts reaching up to ∼140 nm when the volume was decreased. The large red-shift of the plasmon wavelength was ascribed to the increase in the aspect ratio via the selective etching of the Ag nanorods from the necks, which is verified by further etching experiments and electrodynamic simulations. The plasmon wavelength of the etched nanorods can be extended to the entire region of the second biological transparency window by employing different lengths of Ag nanorods with numerous longitudinal dipolar plasmon wavelengths, suggesting the generality of our approach. This study proposes a new nanostructure that can be applied in the near-infrared applications, and it also provides a new route to regulate the plasmon wavelength.